Sustainability Analysis of Farming Roads for Increased Food Security (Case Study on Woro Village, Kepohbaru Subdistrict, Bojonegoro Regency) - Puji Lestari; Arief Rachmansyah; Anthon Efani; Maharani Pertiwi Koentjoro (Postgraduate, University of Mataram, 2023)
Villages are often serve as primary centers for agricultural activities and play a crucial role as the main supporters of national food security. Numerous efforts have been undertaken to food security, with the development of farm road infrastructure being one significant initiative. The village government, aligning with its commitment to support the national program, initiated out the construction of farm roads in 2021-2022. This research explores the sustainability of farm road development with the objective of enhancing agricultural productivity, examining five pillars: environment, social aspects, economic considerations, institutional dimension, and law enforcement. The case analysis on Woro Village in the Kepohbaru District, Bojonegoro Region.A quantitative research methodology was employed, collecting data through a questionnaire distributed to 84 respondents who are members of the village community. The data analysis employed Structural Equation Modeling - Partial Least Squares (SEM-PLS) using SMartPLS 4.0 software. The result is indicated by the path-coefficient values of 0.286; 0.294; 0.351; 0.174; and 0.131; with corresponding t-statistic values of 3.746; 2.517; 3.108, 2.154, and 2.393. The associated p-values were 0.00; 0.012; 0.002; 0.031; and 0.017; respectively. The research findings highlight a notable and positive impact stemming from the five development pillars, namely environment, social, economic, institutional, and law enforcement, on the sustainability of agriculture road development.